OBSERVATIONS ON THE PRAWN FlSHERV OF THE COCHIN BACKWATERS WITH SPECIAL REFERENCE TO THE STAKE NET CATCHES - Menon, M Krishna; Raman, K (Indian Journal of Fisheries, 2011)
The long chain of backwaters extending along the central and southernparts of the Kerala State provides rich prawn fishing grounds, where fishingis carried out practically all the year round. The fishery is not confined tothe backwaters only, but extends into the extensive networks of canalsconnected with them and also to the paddy fields bordering the ' VembanadKayal' at about the middle of the chain. Though reliable statistics areyet lacking there is little doubt that the annual production may amount toseveral thousands of tons.